New synthetic methodologies for the transformation of biomass derived intermediates to valuable molecules - Coelho, Jaime (2016)
Tese de doutoramento, Farmácia (Química Farmacêutica e Terapêutica), Universidade de Lisboa, Faculdade de Farmácia, 2014